2020
DOI: 10.3390/polym13010076
|View full text |Cite
|
Sign up to set email alerts
|

Porous Graphene Composite Polymer Fibres

Abstract: Since the isolation of graphene, there have been boundless pursuits to exploit the many superior properties that this material possesses; nearing the two-decade mark, progress has been made, but more is yet to be done for it to be truly exploited at a commercial scale. Porous graphene (PG) has recently been explored as a promising membrane material for polymer composite fibres. However, controlling the incorporation of high surface area PG into polymer fibres remain largely unexplored. Additionally, most polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 67 publications
1
14
0
Order By: Relevance
“…Fourier-transform infrared (FTIR) spectroscopy is the most common technique for characterizing chemical functional groups present in the polymer nanocomposites. The shift in the IR wavenumbers after functionalization can be qualitatively correlated with the covalent or non-covalent interactions between GDs and AZO moieties [ 117 ]. The major bands that appear in the composites are due to the presence of aromatic rings, AZO chromophores (–N=N–), C–N stretching, along with other bands.…”
Section: Characterization Techniquesmentioning
confidence: 99%
“…Fourier-transform infrared (FTIR) spectroscopy is the most common technique for characterizing chemical functional groups present in the polymer nanocomposites. The shift in the IR wavenumbers after functionalization can be qualitatively correlated with the covalent or non-covalent interactions between GDs and AZO moieties [ 117 ]. The major bands that appear in the composites are due to the presence of aromatic rings, AZO chromophores (–N=N–), C–N stretching, along with other bands.…”
Section: Characterization Techniquesmentioning
confidence: 99%
“…Many studies have been reported on graphene and its derivatives and their nanocomposites discussing antibacterial, antifungal and antiviral activities (18)(19)(20)(40)(41)(42). Matharu et al investigated the antibacterial activity of 2, 4 and 8 w/w% concentration graphene nanoplatelet (GNP) and GO loaded polymethylmethacrylate (PMMA) composite nanofibers against Escherichia coli (E. coli) (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…It is used especially for gas separation and purification applications paying attention to its high permeability ( 44 , 45 ). PG polymer composite nanofibers have been formed using pressurized gyration and the surface topography was studied by Ahmed et al ( 40 ). According to this study, PG was seen as a promising material in ultrafiltration applications ( 40 ).…”
Section: Introductionmentioning
confidence: 99%
“…During the electrochemical action of graphene, the combination of its excellent mechanical strength and high aspect ratio are expected to aid the resulting composite porosity, thereby limiting the cracking and fracture of the electrode [12]. In addition, the chemical and thermal stabilities of graphene are advantageous in the protection from damage of the highly porous electrode [13]. In electrolyte diffusion, graphene, as a good electrical conductor, is an excellent current collector for the passage of ions within the pores of the electrochemical electrodes [14].…”
Section: Introductionmentioning
confidence: 99%
“…Nanomaterials 2021, 11, x FOR PEER REVIEW 2 of 18 [13]. In electrolyte diffusion, graphene, as a good electrical conductor, is an excellent current collector for the passage of ions within the pores of the electrochemical electrodes [14].…”
Section: Introductionmentioning
confidence: 99%